PERAN ORGANIZATIONAL COMMITMENT MEMEDIASI PENGARUH RESPONSIBLE LEADERSHIP TERHADAP EMPLOYEE TURNOVER INTENTIONS - Ni Wayan Eling Juliatri (Ekonomi dan Bisnis, 2021)
High employee turnover intentions can have a negative impact on organizations such as creating instability and uncertainty in the condition of the existing workforce. Many factors influence employee turnover intentions, including responsible leadership and organizational commitment. The purpose of this study was to determine the effect of responsible leadership on employee turnover intentions at PT. Luhur Permai's, either directly or mediated (indirect influence) by organizational commitment. This research was conducted at PT. Karya Luhur Permai In West Denpasar, the sampling in this study was carried out using a random sampling technique, totaling 144 people. Data was collected through interviews and questionnaires. The data analysis technique used is path analysis. Based on the results of the study, it was found that: (1) Responsible leadership has a negative influence on employee turnover intention. (2) Responsible leadership has a positive effect on organizational commitment. (3) Organizational commitment has a negative effect on employee turnover intention. (4) Organizational commitment mediates the effect of responsible leadership on employee turnover intention.